The Effect of Using Peer Editing to Improve Students Ability in Writing at Eight Grade Students of Junior High School of 8 Bukittinggi Academic Year 2018/2019 - Adelia Tufliha (ELITE JOURNAL, 2021)
This research was due to discover the effect of using peer editing to improve students writing. It has been done at SMPN 8 Bukittinggi because some of students in SMPN 8 Bukittinggi still had problems in mastering English especiallyin writing text. Some of the students had a problems in making paragpraph clearly, in organizing their ideas, to found their grammatical or vocabulary error and etc.. This research used experimental research. The researcher used quasi experimental design by using the pretest-posttest design. To determine sample, the researcher used purposive sampling technique. The data was got through pretest and posttest to experimental and control class. To analyze the data, the researcher used the normality by using Lilliefors test and the homogeneity test by using F test and to test the hypothesis the researcher used t-test formula and consulted the result into t-table with level of significant α=0.05.From the result and accounting the pre-test and pos-test scores of experiment class, it was found using peer editing in writing had better result than not using peer editing.